A novel inhibitor of ADAM17 sensitizes colorectal cancer cells to 5‐Fluorouracil by reversing Notch and epithelial‐mesenchymal transition in vitro and in vivo. (2nd August 2018) - Li, Dan‐Dan; Zhao, Chang‐Hao; Ding, Huai‐Wei; Wu, Qiong; Ren, Tian‐Shu; Wang, Jian; Chen, Cong‐Qin; Zhao, Qing‐Chun
Abstract: Objectives: Colorectal cancer is one of the most common malignancies both in men and women. Owing to metastasis and resistance, the prognosis of colorectal cancerCRC patients remains extremely poor with chemotherapy. A disintegrin and metalloproteinase 17 (ADAM17) induces the activation of Notch pathway and contributes to the chemoresistance. This study aimed to discover a novel ADAM17 inhibitor and investigate the chemosensitization effect. Materials and methods: Pharmacophore model, western blot and enzymatic assay were used to discover ZLDI‐8. Cell proliferation was determined by MTT and colony formation assay. Cell migratory and invasive ability were determined by wound healing scratch and transwell assay. Immunofluorescence images and western blot analysed the expression of Notch or epithelial‐mesenchymal transition (EMT) pathway markers. Xenografts were employed to evaluate the chemosensitization effect of ZLDI‐8 in vivo. Results: We found that ZLDI‐8 cell‐specifically inhibited the proliferation of CRC, and this effect was due to abrogation of ADAM17 and Notch pathway. Meanwhile, we reported for the first time that ZLDI‐8 synergistically improved the anti‐tumour and anti‐metastasis activity of 5‐fluorouracil or irinotecan by reversing Notch and EMT pathways. Interestingly, in vivo studies further demonstrated that ZLDI‐8 promoted the anti‐tumour effect of 5‐fluorouracil through Notch and EMT reversal. Conclusions: A novel ADAM17 inhibitor ZLDI‐8 may be a potential chemosensitizer which sensitized CRC cells to 5‐fluorouracil or irinotecan by reversing Notch and EMT pathways.